URGENSI SUMBER DAYA INSANI DALAM MEMBENTUK BUDAYA KERJA ISLAMI - Haryanto, Rudy (Islamuna: Jurnal Studi Islam, 2017)
Individual and organizational activity is a management process undertaken by human resources, no activity can be undertaken without human resources despite the rapid development of tenure at the present time. Organizations or companies make human resources as the primary element in existing resources in the organization or company. Human resources are all holistic human capabilities and capable of using these capabilities to achieve personal and organizational goals in accordance with Islamic Shari'a. So with the conduct of management activities in the element of human resources then every human or employee will perform its duties and functions with amah. With the existence of reliable human resources, the management of the organization or company takes place efficiently and effectively, and ultimately the goal is achieved. Organizational management or human resource based company, making spirituality as the main element and inseparable from the work culture and performance in the organization or Companies to achieve goals. The activity of human resources will achieve the goal that can develop the individual self in person and whole. Attitudes or mental spiritual or muraqabatullah in human resources will have a tremendous impact on the performance of employees and of course also for the capsity of organizations or companies that are efficient and highly competitive.